Proyeksi Penduduk Indonesia dengan menggunakan Metode Campuran - Fadhil Adiwibowo; Yayat Karyana (UNISBA Press, 2022)
Abstract. Badan Pusat Statistik (BPS) has several times made projections of the Indonesian population based on data from the 1971, 1980, 1990, 2000, 2010 Population Census, and based on data from the Survei Penduduk Antar Sensus (SUPAS). This was made in order to fulfill the need for the preparation of Medium Term Development Plans and Long Term Development Plans so that population data was needed until 2045. The population projection methods commonly used are the mathematical method, the component method, and the mixed method. Population projections using the mathematical method are usually used to produce only the total population, while projections using the component method produce the total population and age groups. The mathematical method has a weakness, namely it does not pay attention to demographic components, which include birth, death, and migration. The component method also has a weakness, namely that sometimes the results of the projection are not satisfactory, due to the inaccurate estimation of the migration rate, which changes in each projection period. The mixed method is a combination of the component method and the mathematical method, used to overcome the weaknesses of each method. The mixed method includes the total population taken from the results of the projection using the mathematical method, while the distribution of the population by age group is used from the results of the projection using the component method. Projections of the Indonesian population per 5 years from 2025-2045 using basic data from the 2020 population census, obtained a population of 288,716,143 people, 908,496,679 people, 329,632,420 people, 352,216,214 people, 376,347,271 people. Abstrak. Badan Pusat Statistika (BPS) telah beberapa kali membuat proyeksi penduduk Indonesia berdasarkan data hasil Sensus Penduduk 1971, 1980, 1990, 2000, 2010, dan berdasarkan data hasil Survei Penduduk Antar Sensus (SUPAS). Hal teresebut dibuat dalam rangka memenuhi kebutuhan penyusunan Rencana Pembangunan Jangka Menengah dan Rencana Pembangunan jangka Panjang sehingga diperlukan data kependudukan hingga tahun 2045. Metode proyeksi penduduk yang biasa digunakan adalah metode matematik, metode komponen, metode campuran. Proyeksi penduduk dengan metode matematik biasa digunakan untuk menghasilkan total penduduk saja, sedangkan proyeksi dengan metode komponen menghasilkan total penduduk dan kelompok umur. Metode matematik memiliki kelemahan yaitu tidak memperhatikan komponen demografi yang antara lain kelahiran, kematian, dan migrasi. Metode komponen juga mempunyai kelemahan yaitu terkadang hasil dari proyeksinya kurang memuaskan, karena kurang tepatnya estimasi angka migrasi, yang pada tiap periode proyeksi berubah. Metode campuran merupakan penggabungan dari metode komponen dan metode matematik, digunakan untuk mengatasi kelemahan dari masing masing metode. Metode campuran di dalamnya terdapat total penduduk yang diambil dari hasil proyeksi menggunakan metode matematik sedangkan distribusi penduduk menurut kelompok umur digunakan dari hasil proyeksi menggunakan metode komponen. Proyeksi penduduk Indonesia per 5 tahun dari tahun 2025-2045 dengan menggunakan data dasar hasil sensus penduduk 2020, diperoleh penduduk sebesar 288.716.143 orang, 908.496.679 orang, 329.632.420 orang, 352.216.214 orang, 376.347.271 orang.